Komposisi Gulma Kebun Karet di Kebun Percobaan Cikabayan IPB, Bogor - Maulani, Haris; Alda Wydia Prihartini Azar (Jurnal Biogenerasi, 2025)
Weeds is one of important issues in rubber (Hevea brasilliensis Muell Arg.) plantation. Knowing composition is important so that weed management work effectively, efficiently, and the effects last longer. The aim of this study was to analyze the composition of rubber plantation weeds at Kebun Percobaan Cikabayan. Data collection used the 0.5x0.5 m2 quadrat plot which placed randomly in the rubber plantation area. Names and number of individuals of each species were collected. The crown part of each species was collected to calculate its dry weight. Data were analyzed using vegetation analysis to obtain the ratio of dominant species of each species. The result of this study are the Cikabayan rubber plantation weeds were composed of 7 species of grass weeds and 3 species of broadleaf weeds. Axonopus compressus is the most dominant species with a dominant species ratio value of 42.65%. Keywords: weeds, rubber, composition, dominant species ratio